THE DECOMPOSITION METHODS OF COMPLEX DATA PROCESSING SYSTEMS - Kaziev, G.Z.; Taurbekova, А.А. Taurbekova2 (Academic Journal of Physical and Chemical Sciences, 2018)
This work deals with the mathematical model and algorithm of complex data processing systems decomposition. The task is narrowed down to the discrete programming block-symmetric task. For its solution, taking into account peculiarity of the model, the efficient solution algorithm is suggested.